Study of water diffusion in lymphocyte membranes from thymus gland and spleen of rats by method of quasi-elastic scattering of slow neutrons - Grechko, L.G.; Semchuk, O.Yu.; Bila, R.V.; Slisenko, V.I.; Ostapchenko, L.I. (Поверхность, 2002)
The aqueous suspensions of lymphocyte membranes from the rat thymus gland and spleen cells were studied by the method of a quasi-elastic neutron scattering. Effect of X-ray irradiation on dynamics of water molecules in suspension of such membranes was examined. It was shown that a diffusion coefficient of water molecules decreases with increasing of a dose of X-ray irradiation animals (rats) from 0.5 up to 1.0 Gray.